The number of tries required to win in international rugby sevens - Burdick, B. A. (Journal of Sports Analytics, 2021)
Data from the pool rounds of three HSBC World Rugby Sevens competitions (2016-17, 2017-18, and 2018-19) are used to investigate the number of tries required to win in international rugby sevens. The data consist of 4,391 tries scored in 720 matches (1,440 team performances) and are used to calculate the probability of winning a match given that T tries are scored (P[W|T]). The distribution of the number of tries scored by each team ranges from zero to nine and is shown to be well-represented by a Poisson distribution computed from the mean value of tries scored in that competition. The number of tries scored by the winning team in each match within a competition is well-described by a Gamma function evaluated at the integer number of tries scored with parameters derived from the data set. This appears to be a novel result not previously reported in the literature. Generalizing within each competition, teams scoring either zero tries or one try have less than a 2% chance of winning; those scoring two tries win 10% to 20% of the time; three tries result in nearly a 50% chance of winning; teams scoring four tries are almost sure to win (around 90%); and that for teams scoring five or more tries winning is virtually assured. Based upon the results from these three tournaments we conclude that competitive teams should strive to score three or more tries per match and that there is no winning advantage accrued by scoring more than five tries.